Le mot a l'oreille de Monsieur le marquis de la Vieuille. - Fancan, François Dorval-Langlois; Richelieu, Armand Jean du Plessis (Mot a l'oreille de Monsievr le marqvis de la Vieville, 1624)
"As La Vieuville, Superintendent of Finance, made some financial blunders, a pamphleteering campaign was launched against him. Fancan, one of Richelieu's pamphleteers, wrote this one against him. After La Vieuville was arrested, Richelieu had no rival"--French Political Pamphlets Digital Collection, Brigham Young University.
Variant of Duvall, S.H. French Political Pamphlets Collection at the L. Tom Perry Special Collections, Harold B. Lee Library, Brigham Young University, entry 2020
Variant of Newberry Library. Second checklist of French political pamphlets, 1560-1653, entry *882
Attributed to Fancan by Lindsay and Neu; attributed to Richelieu by Le Long, J. Bibliothèque historique de la France (1768-1778 edition), volume 2, entry 21212
Signatures: A-D⁴.
Le Long, J. Bibliothèque historique de la France (1768-1778 edition),volume 2, entry 21307
Keywords: Economic history. / fast / https://id.worldcat.org/fast/901974; France. / fast / https://id.worldcat.org/fast/1204289; France / Economic conditions / 17th century. / https://id.loc.gov/authorities/subjects/sh85051217; France / Politics and government / 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051466; France / History / Louis XIII, 1610-1643 / https://id.loc.gov/authorities/subjects/sh85051303 / Pamphlets. / https://id.loc.gov/authorities/subjects/sh99001703; Underscoring. / rbmscv / https://id.loc.gov/vocabulary/rbmscv/cv00274; Satires / https://id.loc.gov/vocabulary/rbmscv/cv00917 / France / https://id.loc.gov/authorities/names/n79006404-781 / 17th century. / https://id.loc.gov/authorities/subjects/sh2002012473 / rbmscv; Political satire, French.; Pamphlets / https://vocab.getty.edu/aat/300220572 / France / https://id.loc.gov/authorities/names/n79006404-781 / Seventeenth century (dates CE). / https://vocab.getty.edu/aat/300404511 / aat; Pamphlets. / fast / https://id.worldcat.org/fast/1423837